2018
DOI: 10.1080/21691401.2018.1516671
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of folic acid-functionalized apoferritin as a delivery vehicle for epirubicin against MCF-7 breast cancer cells

Abstract: Epirubicin (Epr) is an effective chemotherapeutic drug; however, the clinical amenability of Epr is limited by its highly toxic interaction with normal cells. This toxicity can be decreased by utilizing nanocarriers and targeted drug delivery systems. This work describes an approach for the delivery of Epr via encapsulation in the horse spleen apoferritin (HsAFr) cavity. The encapsulation was achieved by the disassembling of apoferritin into subunits at pH 2 followed by its reformation at pH 7.4 in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…FA receptors over-expressed MCF-7 cells were used to evaluate the cellular uptake of FA-MMSN-Au/DOX nanoparticles. 34,35 As shown in Figure 5A, free Dox was mainly localized in the nuclei due to its high affinity with DNA. The red fluorescence of DOX appeared in the cytoplasm for FA-MMSN-Au/DOX group, and the fluorescence intensity markedly decreased after preincubation with FA for 2 h, indicating that the target-specific endocytosis of FA-MMSN-Au/DOX was mediated by FA receptors.…”
Section: Cellular Uptakementioning
confidence: 99%
“…FA receptors over-expressed MCF-7 cells were used to evaluate the cellular uptake of FA-MMSN-Au/DOX nanoparticles. 34,35 As shown in Figure 5A, free Dox was mainly localized in the nuclei due to its high affinity with DNA. The red fluorescence of DOX appeared in the cytoplasm for FA-MMSN-Au/DOX group, and the fluorescence intensity markedly decreased after preincubation with FA for 2 h, indicating that the target-specific endocytosis of FA-MMSN-Au/DOX was mediated by FA receptors.…”
Section: Cellular Uptakementioning
confidence: 99%
“…It has already been shown that several drugs, such as cisplatin, streptomycin, doxorubicin, and daunomycin, can be encapsulated in APO [29,30,[37][38][39][40][41][42][43][44][45][46]. Recently, epirubicin-carrying APO nanocarriers have been applied to study MCF-7 breast cancer cells survivability upon nanodrug treatment [47]. Drug encapsulation efficiency of 7.7% has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin is used in a variety of applications such as bioelectronics, 13 biosensing, 14 imaging, 15 water purification, 16 and drug delivery. 17,18 Apoferritin is a ferritin without an iron core. The ferritin has 24 subunits.…”
Section: Introductionmentioning
confidence: 99%